Works councils and employer attitudes toward the incentive effects of HRM practices - Uwe Jirjahn (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2016)
A growing number of econometric examinations show that works councils substantially shape the personnel policy of firms in Germany. Firms with works councils make greater use of various HRM practices. This gives rise to the question of whether employers view the shaping of personnel policy positively or negatively. Using data from manufacturing establishments, this study finds that the incidence of a works council increases the probability that the employer has positive attitudes toward the incentive effects of performance pay, profit sharing, promotions, further training, and worker involvement in decision-making. It decreases the probability of a positive attitude toward the incentive effects of a high-wage policy. The pattern of results also holds when accounting for the issue of endogeneity by applying a recursive multivariate probit model. The results suggest that works councils play a redistribution role in wages and a trust-building role in the other HRM practices.
Keywords: J33; J50; M52; M53; 330; non-union worker representation; management attitude; further training; performance pay; profit sharing; promotions; employee involvement; high wages; recursive multivariate probit model